2009
DOI: 10.1186/gb-2009-10-10-r111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparative analysis of the Brassica rapa gene space reveals genome shrinkage and differential loss of duplicated genes after whole genome triplication

Abstract: Euchromatic regions of the Brassica rapa genome were sequenced and mapped onto the corresponding regions in the Arabidopsis thaliana genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
171
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(192 citation statements)
references
References 65 publications
17
171
1
2
Order By: Relevance
“…Robust molecular cytogenetic karyotypes established for B. rapa, B. oleracea, and B. napus: Numerous molecular cytogenetic studies have reported karyotypes in diploid and amphidiploid Brassica species on mitotic metaphase complements and meiotic prophase (pachytene) chromosomes (e.g., Armstrong et al 1998, Fukui et al 1998Snowdon et al 2002;Koo et al 2004;Lim et al 2005Lim et al , 2007Maluszynska and Hasterok 2005;Howell et al 2008;Kim et al 2009;Mun et al 2009). Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robust molecular cytogenetic karyotypes established for B. rapa, B. oleracea, and B. napus: Numerous molecular cytogenetic studies have reported karyotypes in diploid and amphidiploid Brassica species on mitotic metaphase complements and meiotic prophase (pachytene) chromosomes (e.g., Armstrong et al 1998, Fukui et al 1998Snowdon et al 2002;Koo et al 2004;Lim et al 2005Lim et al , 2007Maluszynska and Hasterok 2005;Howell et al 2008;Kim et al 2009;Mun et al 2009). Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the crop species in the Brassicaceae, the B. rapa genetic, physical, and cytogenetic maps have begun to be integrated by BAC-FISH (Koo et al 2004;Lim et al 2005Lim et al , 2007Yang et al 2007;Kim et al 2009;Mun et al 2009;Xiong et al 2010). However, to our knowledge, a complete karyotype analysis that reliably distinguishes each chromosome in B. oleracea and B. napus has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It includes 119 CC-NBS-LRR genes, 64 TIR-NBS-LRR genes, 34 BED-finger-NBS-LRR, and both truncated and unusual NBS and NBS-LRR-containing genes. Similarly, Mun et al (2009) …”
Section: Organization Of Nbs-lrr Genes In the Plant Genomementioning
confidence: 98%
“…Wide hybridizations are normally performed by the application of embryo rescue techniques. The most recent advances in genome sequencing technology, bioinformatics and data mining have opened an avenue for comparative analysis of ESTs, BACs, genes (families), whole chromosomes and even entire genomes to determine evolutionary relationship between these species and their ancestors (Gao et al, 2004;Gao et al, 2006;Punjabi et al, 2008;Mun et al, 2009;Qiu et al, 2009;Nagoaka et al, 2010). …”
Section: Genomic Relationships In Brassica Speciesmentioning
confidence: 99%